Robust Fusion for Multisensor Multiobject Tracking - Fantacci, C.; Vo, Ba-Ngu; Vo, Ba Tuong; Battistelli, G.; Chisci, L. (Institute of Electrical and Electronics Engineers, 2018)
This letter proposes analytical expressions for the fusion of certain classes of labeled multiobject densities via Kullback-Leibler averaging. Specifically, we provide analytical fusion rules for the labeled multi-Bernoulli and marginalized d-generalized labeled multi-Bernoulli families of labeled multiobject densities. Information fusion via Kullback-Leibler averaging ensures immunity to double counting of information and is essential to the development of effective multiagent multiobject estimation.